2016
DOI: 10.1073/pnas.1607851113
|View full text |Cite
|
Sign up to set email alerts
|

Methylation interactions in Arabidopsis hybrids require RNA-directed DNA methylation and are influenced by genetic variation

Abstract: DNA methylation is a conserved epigenetic mark in plants and many animals. How parental alleles interact in progeny to influence the epigenome is poorly understood. We analyzed the DNA methylomes of Arabidopsis Col and C24 ecotypes, and their hybrid progeny. Hybrids displayed nonadditive DNA methylation levels, termed methylation interactions, throughout the genome. Approximately 2,500 methylation interactions occurred at regions where parental DNA methylation levels are similar, whereas almost 1,000 were at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
113
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 50 publications
6
113
0
Order By: Relevance
“…Both analyses conclude that 24nt siRNAs are important for the initiation of TCM and TCdM events. Zhang et al showed that hybrid vigor is not affected by the abolition of the POLIV/POLV-directed TCM and TCdM events (42). We showed that the altered m C states can affect gene expression but had no evidence that hybrid vigor was affected.…”
Section: Discussionmentioning
confidence: 58%
“…Both analyses conclude that 24nt siRNAs are important for the initiation of TCM and TCdM events. Zhang et al showed that hybrid vigor is not affected by the abolition of the POLIV/POLV-directed TCM and TCdM events (42). We showed that the altered m C states can affect gene expression but had no evidence that hybrid vigor was affected.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, we cannot exclude their importance in establishing a new epigenetic state near TAD3-1 in F1s, leading to the progressive methylation of the Col-0 allele (Fig 5A). Indeed, several reports point toward drastic modifications of sRNA populations between hybrids and their parents, associated with changes in DNA methylation patterns [3235]. Interestingly, regions localized in the vicinity of TEs seem to be particularity prone to changes in sRNA contents [36] and DNA methylation [35] in hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several reports point toward drastic modifications of sRNA populations between hybrids and their parents, associated with changes in DNA methylation patterns [3235]. Interestingly, regions localized in the vicinity of TEs seem to be particularity prone to changes in sRNA contents [36] and DNA methylation [35] in hybrids. Nevertheless, while sRNAs could initiate the spreading of methylation toward TAD3-1 in an initial step, none of the genes involved in 24-nt sRNA synthesis tested in our study (Table 2) are important to maintain the tad3-1 epiallele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hybrid plants, DNA methylation and histone modifications on one chromosome can be transferred to other homologous regions, likely via siRNAs, which can sometimes induce heritable changes of gene expression and phenotypes404142. Paramutation is one such well-known phenomenon, where allelic transfer of epigenetic states occurs in hybrid plants43, and indeed paramutation-like effects have been observed between two T-DNA sequences in Arabidopsis F1 plants1244.…”
Section: Discussionmentioning
confidence: 99%